ANALYSIS OF THE INFLUENCE OF PERSONAL SAFETY PRACTICES, ORGANIZATION AND RESPONSES PERCEIVED BY HEALTH WORKERS ON HOW TO MANAGE THE RISK OF COVID-19 - Dhamanti, Inge; Muhamad, Rosediani; Sari, Luckyta Ayu Puspita (Universitas Airlangga, 2025)
In response to the COVID-19 pandemic, healthcare workers were required to implement safety practices to protect themselves from high transmission risks. The aim of this study is to analyze the influence of personal safety practices, organizational practices, and perceived responses by healthcare workers on how they manage COVID-19 risks. This study is an analytical research using a cross-sectional method. The research instrument used was an online questionnaire distributed in June 2022. The inclusion criteria were healthcare workers serving as frontliners at Community Health Centers (Puskesmas) and Government or Teaching Hospitals in Surabaya City, with a minimum of three months of work experience during the pandemic (2020–2021). A total of 221 respondents participated in the study. The data were analyzed using multiple regression tests to examine the effect of independent variables (perceptions of personal safety practices, organizational practices, and perceived responses related to COVID-19) on the dependent variable (ways of managing COVID-19 risks). The majority of respondents were female (85.5%); 76.5% were married; 88.7% worked at Puskesmas, with 48.4% of them being accredited with full status, and 11.3% worked at hospitals, with 8.1% of those hospitals also fully accredited. This study found that personal safety practices (p = 0.000) and perceived responses (p = 0.025) had a significant effect on how healthcare workers managed COVID-19 risks. Meanwhile, organizational safety practices did not significantly affect risk management. Healthcare facilities need to provide safety training and psychosocial support to enhance healthcare workers’ preparedness and resilience during crises.